"Avdintvm", a new celtiberian verbal form and its possible paradigmatic relations - Jordán Cólera, Carlos (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
The Novallas bronze plaque is a fragmentary text written in Latin alphabet and Celtiberian language whose fi fth line contains the word audintum. The author proposes to analyse it as the genitive plural of the present participle of a verb. The proto-Celtiberian base would be *h2ew-dheh1-/*h2ew-dhh1- or, simply, *audheh1-/*audhh1-. His meaning would be ‘to give, to grant, to donate’. The Celtiberian terms auzeti, auzanto, auz (auzati?) and auzimei may be etymologically related to this stem and possibly so is auzares.
Keywords: Novallas bronce plaque; audintum; Celtiberian epigraphy; Celtiberian language; Celtiberian verb.